Consumption in the Beauty Industry: Factors Influencing Buying Behavior Toward Cruelty-Free Skincare - Catherine Shania Prahandani; Dwinita Laksmidewi (Journal of The Community Development in Asia, 2026)
The growing demand for ethical and sustainable beauty products has heightened consumer interest in cruelty-free skincare, underscoring the need to understand the factors shaping purchasing behavior. This study aims to examine the determinants of buyer behavior toward cruelty-free skincare products by integrating ethical, cognitive, and social factors within the Theory of Planned Behavior (TPB) framework. Using a quantitative approach, data were collected from 216 skincare users in Indonesia, predominantly young and urban consumers. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was employed to test the proposed relationships. The results reveal that attitude toward cruelty-free skincare has a strong and significant effect on buyer behavior (? = 0.740, p 0.001). Environmental knowledge (? = 0.233, p = 0.008), subjective norms (? = 0.270, p = 0.006), and altruism (? = 0.343, p 0.001) positively influence attitude, whereas personal appearance concern shows no significant effect (? = 0.059, p = 0.315). These findings reinforce the relevance of TPB in explaining ethical skincare consumption and extend prior studies by highlighting the importance of moral awareness, social influence, and environmental knowledge in shaping ethical purchasing behavior in an emerging market context.